Didactics of Children’s Literature in Light of the Ljubljana Manifesto: Advanced Reading and Developing Empathetic Ability (Preučevanje otroške in mladinske književnosti, 2025)
Slovenia highlighted the importance of deep reading for critical thinking, cognitive empathy, and social skills at the Ljubljana manifesto. This paper explores the preparedness of youth literature didactics for these challenges. We examine three case studies that utilize various literary-didactic methods to develop the ability to perceive and adopt literary characters' perspectives. The first study involves role-playing and diary writing, the second combines serial reading and diary writing, and the third focuses on perspective-taking through problem-based literature. The results indicate that these methods effectively promote the development of empathetic abilities in students. We conclude that youth literature didactics are prepared for these challenges, as literary-didactic methods successfully develop the abilities to perceive, understand, and evaluate literary perspectives and related empathetic skills.